Percutaneous coronary intervention in side branch coronary arteries: Insights from the Japanese nationwide registry - Yoshinobu Murasato (International Journal of Cardiology: Heart & Vasculature, 2021)
Background: Performance of percutaneous coronary intervention (PCI) in side-branch vessels (SB-PCI) has not been fully investigated despite the technical advancement of PCI. Methods: We investigated 257,492 patients registered in the Japanese nationwide PCI registry from January to December 2018; 199,767 (78%) underwent PCI for major vessel PCI (MV-PCI), 21,555 (8.4%) underwent SB-PCI, and 24,862 (9.6%) underwent PCI for both vessels (SB + MV-PCI). The frequencies of primary composite adverse events, defined as in-hospital mortality and procedural complications (i.e., peri-procedural myocardial infarction, tamponade, new-onset cardiogenic shock, stent thrombosis, emergent surgery, and bleeding), and PCI for restenotic lesions were investigated. Their association with institutional frequency of each PCI was also investigated. Results: Fewer drug-eluting stents (66% vs. 86%) and more drug-coated balloons (23% vs. 9%) were used in SB-PCI than in MV-PCI (p < 0.001). Pre-procedure non-invasive testing was similarly performed in SB-PCI and MV-PCI (57% vs. 61%). The composite endpoint was observed in 0.7%, 1.9%, and 2.2% of the SB-PCI, SB + MV-PCI, and MV-PCI groups, respectively (p < 0.001). Institutional frequency of SB-PCI was inversely associated with the composite-endpoint risk for all PCI procedures (odds ratio 1.37, 95% confidence interval 1.04–1.81 in the lowest tertile, with reference to the middle tertile, p = 0.02). Frequency of PCI for restenotic lesions was also inversely associated with the institutional frequency of MV-PCI (p < 0.001). Conclusion: SB-PCI was performed safely with a low frequency of acute complications, and higher SB-PCI frequency presented a lower risk of in-hospital adverse events, albeit with a cost of an increase in PCI for restenotic lesions.